Eastern Cherry Fruit Fly, Rhagoletis cingulata (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr. (EDIS)
Larvae of two closely related species of fruit flies in central and eastern North America -- Rhagoletis cingulata (Loew), commonly called the cherry fruit fly or cherry maggot, and Rhagoletis fausta (Osten Sacken), the black cherry fruit fly -- attack cherry and cause wormy fruits. Only R. cingulata occurs in Florida, where it attacks wild cherries and is of little economic importance. These two species closely resemble a third pest species, the apple maggot, Rhagoletis pomonella (Walsh); the adults of all three have banded wings. R. cingulata breeds in all varieties of cherries including the sweet cherry. This document is EENY-203 (originally published as DPI Entomology Circular 116), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001.